Penerapan Sistem Akuntansi Pada PT Mitra Perkasa Harapan - O.Feriyanto; Riska Saumira Amanda; Citra Rahayu; Lusiana Lusiana; Okeu Kusmayanti; Shalma Ayu Miranda P (Journal Economic Excellence Ibnu Sina, 2024)
The accounting information system is an integral part of the overall system formed and implemented by a company. The long-term success of a company heavily depends on the effectiveness of the accounting information system used. PT Mitra Perkasa Harapan, a company engaged in the production and sale of foam mattresses, requires an appropriate accounting information system to support its operations. This research aims to evaluate the implementation of the Accounting Information System at PT Mitra Perkasa and find the best ways to improve it according to the correct procedures. This research utilizes the analytical descriptive method, which involves collecting relevant data and information to be analyzed to reach accurate conclusions. Data collection is conducted through interviews and observations. The research findings indicate that the implementation of the Accounting Information System at PT Mitra Perkasa is still not optimal, as evidenced by the dual roles played by several functions within the organization. To achieve efficiency and compliance with the correct procedures, adjustments are needed in managing the accounting information system. Improvement measures should be based on careful analysis and interdepartmental coordination to ensure that the implemented system aligns with the company's needs and established standards. Consequently, the company can enhance its operational performance and better achieve its long-term goals.